Eocene southern Atlantic Ocean dinoflagellate cysts: regional correlation and paleoenvironments - Daners, G.; Rodriguez Amenabar, Cecilia; Alperin, Marta Ines; Guerstein, Gladys Raquel
The Eocene was a time of regional tectonic events and climatological changes, related to the opening of the Drake Passage that separated South America from Antarctica. Knowledge of the timing of the Drake rifting can help us understand the new oceanographic regime and its consequences. In this sense, dinoflagellate cysts (dinocysts) are useful tools for biostratigraphy and palaeoceanographic reconstructions. For this purpose, we analyzed dinocyst assemblages from lithostratigraphic units adjacent to the Drake Passage, including the Man Aike (MA), the Upper Member of the Río Turbio (umRT) and Leticia (Le) formations, outcropping in the Austral-Magallanes Basin, southern Patagonia, and the La Meseta Formation (LM), from the James Ross Basin, Antarctica. Our quantitative information of the dinocyst assemblages of the aforementioned units together with the recently published radiometric data were taken into account to update the biostratigraphic scheme for the Austral-Magallanes Basin, adjusting the ages of the dinocyst biozones and bioevents proposed for the umRT. The statistical compositional analysis of the quantitative dinocyst assemblages performed in this work allowed us to confirm the correlation of the formations, showing a high equivalence between the middle Eocene (Bartonian, 41 ˗ 37 Ma) assemblages (lower part of the umRT, MA, Le and LM) separating from the late Eocene (< 36 Ma) ones (upper part of the umRT). In addition, the statistical results revealed different palaeoenvironments. While the Bartonian assemblages represent relatively warm waters in inland shelf environments, those of the Priabonian indicated coastal areas with cold, nutrient-rich surface waters. Fil: Daners, G. Universidad de la Republica Montevideo; Uruguay Fil: Rodriguez Amenabar, Cecilia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. ...